The legend of Sleepy Hollow, and Rip Van Winkle - Irving, Washington 1783-1859.; Kelly, Jack.; Marcos, Pablo (New York Baronet Books, 1995)
In the first of these stories from the Catskill Mountains, a superstitious schoolmaster encounters a headless horseman; in the second, a man sleeps for twenty years, waking to a much-changed world.
Keywords: Children's stories, American; Short stories; Catskill Mountains Region (N.Y.) -- History -- 18th century -- Fiction; New York (State) -- History -- 1775-1865 -- Fiction